KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA BERDASARKAN GAYA BELAJAR - Imamuddin, M (Al-Khawarizmi, 2019)
One of the goals of mathematics learning according to the content standards of mathematics is that students have the ability to solve problems that include the ability to understand problems, design mathematical models, complete models and interpret solutions obtained. So that students from elementary school to university level have been trained in mathematical problem solving questions. However, there are still many weak students in achievement in the field of mathematics such as problem solving skills. One of the factors that influence the weakness of problem solving skills is the learning style. The purpose of this study was to analyze students' mathematical problem solving abilities based on learning styles. The type of this research is descriptive quantitative, with the research subject being students of class VIII MTsN totaling 38 students. The instrument used is Questionnaire and Test the ability to solve mathematical problems. Questionnaires are used to classify student learning styles, while problem solving ability tests are used to analyze students' problem solving abilities. The results of the study concluded that mathematical problem solving abilities of students who had a visual learning style were higher than the mathematical problem solving abilities of students who had audiotorial and kinesthetic learning styles. And the ability of problem solving students who have audiotorial learning styles is higher than students who have kinesthetic learning styles.